A New Pd Doped Proton Conducting Perovskite Oxide with Multiple Functionalities for Efficient and Stable Power Generation from Ammonia at Reduced Temperatures. Issue 19 (29th March 2021) - He, Fan; Gao, Qinning; Liu, Zuoqing; Yang, Meiting; Ran, Ran; Yang, Guangming; Wang, Wei; Zhou, Wei; Shao, Zongping
Abstract: The combination of ammonia fuel and proton‐conducting fuel cells (PCFCs) technology may provide an ideal clean energy system for the future, considering matured NH3 synthesis technology and transportation and storage infrastructure, the high energy density of NH3, and the high efficiency of fuel cells. However, poor catalytic activity of the anode for NH3 decomposition, quick performance degradation due to the ammonia induced nickel coarsening, difficult sintering, and insufficient proton conductivity of electrolytes are the main challenges for stable and high‐power generation from ammonia‐fueled PCFCs. Herein, a new Ba(Zr0.1 Ce0.7 Y0.1 Yb0.1 )0.95 Pd0.05 O3− δ perovskite is reported as a key anode component and electrolyte, which demonstrates multifunctionalities and tackles most challenges of conventional PCFCs. The incorporation of a small amount of Pd boosts catalytic activity of the nickel‐perovskite cermet anode for NH3 decomposition and increases proton conductivity from the creation of B‐site cation deficiency and electrolyte sintering. The corresponding thin‐film electrolyte PCFC delivers a maximum power density of 724 mW cm –2 at 650 °C operated on NH3, much higher than the similar cell without Pd incorporation (450 mW cm –2 ). Furthermore, no apparent performance decay is observed for the cell operated at 550 °C in H2 and NH3 for 350 h, making it highly promising for practical applications. Abstract : Pd doped into BaZr0.1 Ce0.7 Y0.1 Yb0.1 O3− δ boosts the activity of anodes for NH3 decomposition and increases proton conductivity from the creation of B‐site cation deficiency and electrolyte sintering. The exsolved Pd acts as the proton supply and protects Ni from the destruction of high NH3 concentration. Therefore, stable performance of a proton‐conducting fuel cell in H2 and NH3 is obtained.